Familial cortical dysplasia caused by mutation in the mammalian target of rapamycin regulator NPRL3. Issue 1 (12th December 2015) - Sim, Joe C.; Scerri, Thomas; Fanjul‐Fernández, Miriam; Riseley, Jessica R.; Gillies, Greta; Pope, Kate; van Roozendaal, Hanna; Heng, Julian I.; Mandelstam, Simone A.; McGillivray, George; MacGregor, Duncan; Kannan, Lakshminarayanan; et al.
Abstract : We describe first cousin sibling pairs with focal epilepsy, one of each pair having focal cortical dysplasia (FCD) IIa. Linkage analysis and whole‐exome sequencing identified a heterozygous germline frameshift mutation in the gene encoding nitrogen permease regulator‐like 3 ( NPRL3) . NPRL3 is a component of GAP Activity Towards Rags 1, a negative regulator of the mammalian target of rapamycin complex 1 signaling pathway. Immunostaining of resected brain tissue demonstrated mammalian target of rapamycin activation. Screening of 52 unrelated individuals with FCD identified 2 additional patients with FCDIIa and germline NPRL3 mutations. Similar to DEPDC5, NPRL3 mutations may be considered as causal variants in patients with FCD or magnetic resonance imaging–negative focal epilepsy. ANN NEUROL 2016;79:132–137